Gestualna ekspresija in njena artikulacija v umetnosti - Kovačev, Asja Nina (Psihološka obzorja (Ljubljana), 1995)
Man is the most expressive living being. His psychic processes can be controlled consciously and articulated intentionally. The first forms of his self-expression are the spontaneous vocal and gestural ones. On higher levels of development they are organized further. The highest product of his expressive activity is art. Artistic expression in the plastic arts is a very special form of articulate gestural expression, which can be identified with the registration of spontaneous and articulated gestures on the canvas. A typical example of their registration is action painting. It namely loosens the subject's gestural expression completely. Gesture is explained as an irrational hand movement which enables the spontaneous expression of the painter's inner world.
Keywords: geste; neverbalne komunikacije; čustva; artikulacija; art of painting; slikarstvo; umetnost; art; simbolika